2021
DOI: 10.3389/fclim.2021.738286
|View full text |Cite
|
Sign up to set email alerts
|

Financing the Transition Toward Carbon Neutrality—an Agent-Based Approach to Modeling Investment Decisions in the Electricity System

Abstract: Transitioning to a low-carbon electricity system requires investments on a very large scale. These investments require access to capital, but that access can be challenging to obtain. Most energy system models do not (explicitly) model investment financing and thereby fail to take this challenge into account. In this study, we develop an agent-based model, where we explicitly include power sector investment financing. We find that different levels of financing constraints and capital availabilities noticeably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…To solve the uncoordinated problem between carbon mitigation and the economic performance of enterprises, the ESG (environmental, social, and governance) strategy has been put forward, which suggests that a coordinated mechanism of carbon emission rights and carbon tax should be established to encourage clean energy development by subsidizing R&D in the fossil fuel industry with tax incentives or tax rebates (Fragkos et al, 2017;Su et al, 2021;. Yang et al (2021) found that carbon emissions are cut more rapidly when the carbon tax grows faster. That is, the carbon tax could stimulate green investment in the electricity system and affect carbon mitigation, but there is overall a greater tendency for agents to go bankrupt when the tax grows faster.…”
Section: Literature Review Of Carbon Decision Between the Government ...mentioning
confidence: 99%
“…To solve the uncoordinated problem between carbon mitigation and the economic performance of enterprises, the ESG (environmental, social, and governance) strategy has been put forward, which suggests that a coordinated mechanism of carbon emission rights and carbon tax should be established to encourage clean energy development by subsidizing R&D in the fossil fuel industry with tax incentives or tax rebates (Fragkos et al, 2017;Su et al, 2021;. Yang et al (2021) found that carbon emissions are cut more rapidly when the carbon tax grows faster. That is, the carbon tax could stimulate green investment in the electricity system and affect carbon mitigation, but there is overall a greater tendency for agents to go bankrupt when the tax grows faster.…”
Section: Literature Review Of Carbon Decision Between the Government ...mentioning
confidence: 99%